Pengembangan model pembelajaran scientific untuk meningkatkan ketuntasan belajar bahasa Inggris tema “recount text” deskriptif lisan dan tulis, pendek dan sederhana, tentang orang, binatang, dan benda di kelas 8 MTs Negeri Sooko Mojokerto - Rodhi, Mohammad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
The process of scientific work, promoting inductive reasoning rather than deductive reasoning. Inductive reasoning sees a specific phenomenon or situation to then draw an overall conclusion. Especially in the learning of Writing (writing), some things are perceived as a constraint of them is that this learning requires careful planning so that students can achieve basic competence indicator. The purpose of this research development is: 1) Describe the learning tools developed in the model of scientific learning to improve the completeness of learning English the theme of